2020
DOI: 10.1016/j.jhepr.2020.100150
|View full text |Cite
|
Sign up to set email alerts
|

Association between remnant lipoprotein cholesterol levels and non-alcoholic fatty liver disease in adolescents

Abstract: Non-alcoholic fatty liver disease (NAFLD) and heart disease share risk factors. Serum remnant lipoprotein cholesterol (RLP-C) is linked with severity of liver fat. Males with NAFLD have higher cardiometabolic risk. RLP-C may contribute to risk of cardiovascular disease in people with NAFLD. Lay summary Remnant lipoprotein cholesterol (RLP-C) is a part of the blood cholesterol that is linked with heart disease and non-alcoholic fatty liver disease (NAFLD) in adults. In the Raine Study, teenagers with high RLP-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
2
14
0
3
Order By: Relevance
“…Recently, there have been several reports on the relationship between RC and NAFLD. In 2018, Pastori et al found for the first time that higher levels of RC were independently positively correlated with NAFLD in patients with cardiac metabolic diseases [ 37 ], and Chin et al also found a similar association in adolescents [ 38 ]. This conclusion was validated in this study, and the findings of this study support the role of RC as an independent risk factor for NAFLD in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been several reports on the relationship between RC and NAFLD. In 2018, Pastori et al found for the first time that higher levels of RC were independently positively correlated with NAFLD in patients with cardiac metabolic diseases [ 37 ], and Chin et al also found a similar association in adolescents [ 38 ]. This conclusion was validated in this study, and the findings of this study support the role of RC as an independent risk factor for NAFLD in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…VLDL synthesis is impaired in NASH, possibly as the result of lipid oxidative DNA damage, leading to dysfunctional VLDL synthesis and lipid outflow as key factors in the progression to NASH 117 . In the context of TG‐rich lipoproteins, fasting remnant‐cholesterol, another CV risk factor, is associated with the odds of NAFLD beyond traditional risk factors, such as adiposity and IR 118 . Fatty liver and elevated TG can be finally linked to apoprotein C3 ( APOC3 ) variant alleles (C482T, T455C or both).…”
Section: Nafld and Risk Of Cardiovascular Diseasesmentioning
confidence: 99%
“…Отримані в нашому дослідженні результати узгоджуються з даними інших авторів [4,9,11]. Так, визначено, що при коморбідному поєднанні НАЖХП і ГХ та ізольованій НАЖХП медіана ІМТ статистично значущо переважала показники контрольної групи (відповідно 27,8 [26,6; 28,5] кг/м 2 ; р < 0,001; 27,3 [24,2; 28,3] кг/ м 2 ; р = 0,004 та 24,3 [21,9; 26,0] кг/ м 2 ).…”
Section: результати та обговоренняunclassified
“…Chin та співавт. [4] у дослідженні з участю 108 хворих на цукровий діабет і НАЖХП виявили наявність статистично значущого (p < 0,05) зв'язку ІМТ, САТ і ДАТ з розвитком фіброзу на тлі НАЖХП та статистично значуще збільшення показників ІМТ, САТ і ДАТ у хворих як чоловічої (відповідно (29,3 ± 5,9) кг/ м 2 , (124,3 ± 9,8) та (60,2 ± 7,1) мм рт. ст.…”
Section: результати та обговоренняunclassified
See 1 more Smart Citation